2014
DOI: 10.18632/oncotarget.2368
|View full text |Cite
|
Sign up to set email alerts
|

IL-6-stimulated CD11b+CD14+HLA-DR− myeloid-derived suppressor cells, are associated with progression and poor prognosis in squamous cell carcinoma of the esophagus

Abstract: The aim of this study was to assess the significance of myeloid-derived suppressor cells (MDSCs) and their association with IL-6 in esophageal squamous cell carcinoma (SCC). We examined the percentage of CD11b+CD14+HLA-DR− myeloid cells and the levels of IL-6 in the peripheral blood of 50 patients with esophageal SCC and 12 healthy controls. Moreover, we evaluated the relationship between MDSC recruitment, IL-6 levels, and tumor progression by adding 4-nitroquinoline 1-oxide (4-NQO) to the drinking water of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 137 publications
(133 citation statements)
references
References 43 publications
6
126
1
Order By: Relevance
“…S5), calcitriol significantly attenuated the increased IL6 noted in 4-NQO-treated mice, including serum and esophageal lesions. We previously reported that IL6 is associated with MDSC accumulation and invasive tumor progression in vivo (21). Moreover, our data suggested that the inhibition of IL6 was linked to the antitumor effect induced by calcitriol.…”
Section: Effect Of Calcitriol On Tumor Progression In Vivo and Its LIsupporting
confidence: 56%
See 4 more Smart Citations
“…S5), calcitriol significantly attenuated the increased IL6 noted in 4-NQO-treated mice, including serum and esophageal lesions. We previously reported that IL6 is associated with MDSC accumulation and invasive tumor progression in vivo (21). Moreover, our data suggested that the inhibition of IL6 was linked to the antitumor effect induced by calcitriol.…”
Section: Effect Of Calcitriol On Tumor Progression In Vivo and Its LIsupporting
confidence: 56%
“…Many of these approaches are likely to be most effective in immunocompetent tumor-bearing individuals who are minimally immunosuppressed. IL6 has been reported linked with the recruitment of MDSCs and tumor progression in esophageal SCC (20,21). MDSCs constitute an immature population of myeloid cells thought to be an important subset of cells that contribute to an immunosuppressive tumor microenvironment (43,44) and are significantly increased in number in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations